Emotional profile of athletes before competition: contributions for perceived stress, cognitive appraisal and coping strategies - Nogueira, J. M.; Morais, C.; Mansell, P.; Gomes, R. (Frontiers in Sports and Active Living, 2025)
Introduction: Understanding athletes' emotional experience prior to competition is crucial for examining their adaptation to stress. Earlier research suggested anxiety impaired performance by disrupting tasks like information processing, attention, and concentration—leading to increased stress and perceived threat. Over time, focus shifted toward understanding how athletes' interpretations of anxiety could influence performance positively. This led to broader research into other emotions typically considered "negative" (e.g., anger, dejection) and "positive" (e.g., excitement, happiness). However, how these emotions influence performance and interact with intensity has been under-studied.